2016
DOI: 10.1213/xaa.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotic Management of Surgical Patients Noted as “Allergic” to Penicillin at Two Academic Hospitals

Abstract: We studied prophylactic antibiotics administered at 2 academic medical centers during a 6-year period where a cephalosporin was indicated but an "allergy" to penicillin was noted. Another drug (typically vancomycin or clindamycin) was substituted approximately 80% of the time; this occurred frequently even when symptoms unrelated to acute hypersensitivity were listed. In >50% of cases, the reaction was either omitted or vague (e.g., simply "rash"). Given the estimated 1% cross-reactivity between penicillins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Although approximately 85% of procedures used the first-line recommended antibiotic cefazolin, patients reporting a penicillin allergy rarely received cefazolin and instead were 8-16 times more likely than those without a penicillin allergy history to receive clindamycin, vancomycin, or gentamicin. Prior studies reported similar patterns of antibiotic prophylaxis use among those with a reported penicillin allergy [18][19][20][21]. Patients with reported penicillin allergy in this study were not only less likely to receive the most effective perioperative antibiotic, they were also less likely to receive prophylaxis in the recommended time-frame for optimal tissue concentration, especially when vancomycin was the alternative antibiotic administered.…”
Section: Discusssionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although approximately 85% of procedures used the first-line recommended antibiotic cefazolin, patients reporting a penicillin allergy rarely received cefazolin and instead were 8-16 times more likely than those without a penicillin allergy history to receive clindamycin, vancomycin, or gentamicin. Prior studies reported similar patterns of antibiotic prophylaxis use among those with a reported penicillin allergy [18][19][20][21]. Patients with reported penicillin allergy in this study were not only less likely to receive the most effective perioperative antibiotic, they were also less likely to receive prophylaxis in the recommended time-frame for optimal tissue concentration, especially when vancomycin was the alternative antibiotic administered.…”
Section: Discusssionsupporting
confidence: 57%
“…Cefazolin, a first-generation cephalosporin antibiotic, is often the recommended drug due to its spectrum of coverage (ie, activity against common skin flora, including methicillin-sensitive Staphylococcus aureus [MSSA] and Streptococcus species), bactericidal activity, and favorable pharmacokinetics whereby the drug rapidly reaches optimal antibacterial concentrations in tissues [13][14][15]. For the 10% of patients who report a prior penicillin allergy [16,17], non-betalactam antibiotics (eg, clindamycin, vancomycin) may be administered [18][19][20][21]. This is despite evidence demonstrating that 90%-99% of patients with a reported penicillin allergy are not truly allergic (ie, there is no immediate hypersensitivity) and <3% of patients with an allergy to penicillin will also react to cefazolin [22][23][24][25].…”
mentioning
confidence: 99%
“…Only one patient had an allergic reaction (0.3%) [63]. In an intraoperative antibiotic study looking at patients with reported penicillin allergies and who were given a cephalosporin, none of the 6067 patients were reported to have an allergic reaction [85]. In another peri-operative antibiotic study in penicillin allergic patients, a total of 513 allergic patients were identified, encompassing 624 surgical patients.…”
Section: Cephalosporin Cross-reactivitymentioning
confidence: 99%
“…Patients with septic shock can be identified with a clinical construct of sepsis with persisting hypotension requiring vasopressors to maintain MAP 65 mm Hg and having serum lactate level > 2 mmol/L (18 mg/dL) despite adequate volume resuscitation; with these criteria, hospital mortality rate is in excess of 40% (13) bronchospasm, pulmonary edema, laryngospasm, and hypotension is relatively uncommon, occurring in approximately 2% of the general population (32). Although natural penicillins such as penicillin G or VK are uncommonly used in IR, their semisynthetic derivatives such as amoxicillin, ampicillin, and piperacillin should be avoided in patients with a true penicillin allergy.…”
Section: Penicillin Allergymentioning
confidence: 99%
“…Although natural penicillins such as penicillin G or VK are uncommonly used in IR, their semisynthetic derivatives such as amoxicillin, ampicillin, and piperacillin should be avoided in patients with a true penicillin allergy. In such patients, agents without the b-lactam ring, such as vancomycin, clindamycin, or carbapenems, can be used as alternatives, keeping in mind their added cost and broader spectrum (32,33). The incidence of cross-reactivity between cephalosporins and penicillin has historically been reported to be approximately 10% (34).…”
Section: Penicillin Allergymentioning
confidence: 99%